WhatsApp and audio misinformation during the Covid-19 pandemic - Cardoso, G. (2022)
Given user choices and the commercial offerings of internet providers, WhatsApp has increasingly become established as a new standard for communication by audio, image, and text. This paper explores the role of misinformation during the Covid-19 pandemic by using content disseminated through WhatsApp, thereby making three main contributions: a discussion about the potential shift toward nontextual and nonvisual forms of misinformation; the new social role of audio, namely related to the critique of policies and political actors during the early stage of the Covid-19 pandemic; and the questioning of the First Draft News disinformation conceptual model by proposing a complementary approach that focuses only on factuality. Conclusions were drawn after conducting a content analysis of 988 units of Covid-19-related audio files, images, videos, and texts shared via WhatsApp during the early stage of the pandemic. A typology was identified to address distinct claims that focus on five different topics (society, policy and politics, health science, pandemic, and other), as well as audio messaging trending as a novel format for spreading misinformation. The results help us to contextualize and discuss a potential shift toward nontextual and nonvisual forms of misinformation, reflecting the increasing adoption of the audio format among WhatsApp users and making WhatsApp a fertile environment for the circulation and dissemination of misinformation regarding Covid-19-related themes. In a society characterized by the rapid consumption of information, the idea that content must have a degree of falsehood to mislead is an indicator of the distance between theoretical models and social reality. This indicator is important to identify true content as potential misinformation on the basis of its factuality.